The thermodynamic properties of the alloys of the systems Si – РЗМ and Si – Al – РЗМ - Матейко, І.; Судавцова, В.; Котова, Н.; Шаркіна, Н. (Київський національний університет імені Тараса Шевченка, 2008)
The thermochemical properties of melts of binary systems Si – Dy(Ho, Er)  and three-component systems Si – Al – Dy(Ho, Er) along one –  two cuts for each system at 1880 ±  10 К are studied by the method of a calorimetry in the isothermal hyperthermal calorimeter. Established, that all studied alloys will be derivated with allocation of a significant amount of a heat. In all an interval of structures the thermochemical properties are counted from the data for double boundary systems on equations Bonnier-Cabo, Tup, Colier.

Методом калориметрії в ізотермічному високотемпературному калориметрі досліджені термохімічні властивості розплавів двокомпонентних систем Si – Dy(Ho, Er) і трикомпонентних систем Si – Al – Dy(Ho, Er) вздовж одного – двох перерізів для кожної системи при 1800 ± 10 К. Встановлено, що всі вивчені сплави утворюються із виділенням значної кількості теплоти. У всьому інтервалі складів розраховані термохімічні властивості за рівняннями Боньє-Кабо, Тупа, Колера з даних для подвійних граничних систем.
Термодинамічні властивості розплавів систем Si – РЗМ i Si – Al – РЗМ
Keywords: -; -; -